Settler indignity in the West Bank - McGonigle, Ian (McGill Queens University Press, 2023)
Since Israel conquered the West Bank, formerly held by Jordan, in 1967, over 400,000 settlers have moved into the territory. In recent years, Israeli settler organizations and allied American-Jewish lobbyists have responded to international condemnation of the occupation by mobilizing narratives of indigeneity, claiming sovereign and divine rights to the land.